Air Leak into the Soft Tissues During the Puffed Cheek CT Evaluation of Oral Cavity: Diagnosis and Implication of a Rare Phenomenon - Bhat, Venkatraman (J Maxillofac Oral Surg, 2016)
Leakage of small pockets of air in to soft tissues of cheek along vascular bundle is reported in a patient with ulcerated oral malignancy with history of recent biopsy. Leakage occurred during an attempt to puff the cheek during CT examination of oral cavity. Hereto undocumented phenomenon was self limiting and did not lead to clinical disability. Imaging appearance and likely mechanism of the complication are discussed.